PENGARUH KAPASITAS FISKAL TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA PEMERINTAHAN KOTA / KABUPATEN DI SUMATERA UTARA - Marbun, Gembira (UNIKA Santo Thomas, 2010)
This research aim to know influance of fiscal capacity (Pendapatan Asli Daerah, Dana Alokasi Umum and Dana Bagi Hasil ) to the Human Development Index. Scope of research are 33 ( thirty three) local government in Sumatera Utara. Comply with criteria for sampling source it 25 (twenty five) local government in Sumatera Utara Province. Sample taking with purposive method sampling with period of research between of 2005 up to year of 2009. The data using to independent variable of by 2005-2008, and HDI data used of 2006-2009. Analysis method the used is Generalized Least Square (GLS) with random effect model estimation. The Simultanly of fiscal capacity variable (Pendapatan Asli Daerah, Dana Alokasi Umum and Sharing Dana Bagi Hasil) influance to the Human Development Index. Partially shown that only of Dana Alokasi Umum variable significance to the Human Development Index variable. But, other variable of fiscal capacity variable (Pendapatan Asli Daerah and Dana Bagi Hasil ) not influance to the Human Development Index